The Society’s Perception towards the Impact of University Students Goes to Children Community - Diana Achmad; Asnawi Muslem; Riki Muhamanda (Proceedings of AICS - Social Sciences, 2021)
This study aims to determine the perception of society on the impact of the University Student Goes to Children (US Goes to Children) community-based teaching program in improving the English competence among young village learners. The data were collected from the communities found in four villages: Lampermai, Kahju, Gampong Jawa, and Darussalam. The findings show that the community-based teaching program fosters positive relationships with the villagers and children in the research locale. The program was able to advocate positive outcomes through a method called Fun-Game-Award. Thus, the parents knew what kinds of activities their children were involved in. Some of the activities done by the teaching community were playing guessing games, singing songs, and telling stories. The results indicated positive perception for the participating community groups which makes it a viable mechanism in teaching English language competence among villagers.Keywords: US Goes to Children, Fun Game Award, society’s perception, young learners.